UZBEKISTAN’S TRANSITION TO A GREEN ECONOMY: CHALLENGES, ACHIEVEMENTS, AND PROSPECTS (World Economics and Finance Bulletin, 2025)
This article analyzes the current state and prospect of the transition of Uzbekistan to environmentally harmful economics. At the beginning of the article, attention is drawn to the personnel potential in this area, the second part of the article is devoted to comparing different studies related to the improvement of the country's environmental condition. Also, the article lists the measures already taken by the state in the form of an increase in investment and international cooperation.